(untitled) (Al-Aasar, 2025)
Language, though seemingly simple, is complex in structure and function. Linguists analyze its significance, evolution, and role in communication. The distinction between language and dialect is based on standardization and social acceptance. A dialect is a regional or social variation of a language; when widely recognized, it evolves into a formal language. Dialects often lack literary tradition or institutional support, preventing them from becoming full-fledged languages. Every language originates as a dialect and evolves over time, influenced by social, cultural, and regional factors. Linguistic diversity results from variations in pronunciation, vocabulary, and usage across different communities. Ultimately, language is a dynamic system shaped by its speakers, where dialects contribute to its richness and adaptability.